Occupants' satisfaction on internal layout of low- cost high rise housing in Kuala Lumpur / Muhammad Firdaus Anuar and Rohaslinda Ramele - Anuar, Muhammad Firdaus; Ramele, Rohaslinda (Faculty of Architecture, Planning and Surveying, 2017)
The effort to improve the aspect of designing low-cost houses in Malaysia is still abandoned and neglected. The main reason contributing to this factor is due to the low price value; however, occupant's needs and desires should also be considered thus to achieve the level of satisfaction in term of comfortable living environment. This paper assesses the occupants' satisfaction on internal layout of low-cost high rise housing in Kuala Lumpur, Malaysia. The purpose of the study is to improve internal layout of low-cost high rise housing by investigating current internal layout of low-cost high rise housing in Malaysia and determining the level of occupant's satisfaction. The research was done by using quantitative and qualitative approach, where Program Perumahan Rakyat Kampung Limau and Perumahan Awam Putra Ria were selected as the case study. The results showed that the internal layout of low-cost high rise housing is still poor in meeting occupants' needs and desires especially in term of house area, location of room, function, architectural finishes, materials selection and proofing system. Due to these issues, the low level of satisfaction among occupants in Program Perumahan Rakyat Kampung Limau is recorded as compared to occupants in Perumahan Awam Putra Ria. Occupants were dissatisfied with the size and arrangement of bedroom 3, toilet and dry yard, material used for window and also sound insulation of house. Hence, some recommendations on internal layout of house are identified to increase the level of occupants' satisfaction. This research indicates the importance of occupants' satisfaction on improving the internal layout for future development of low-cost high rise housing in Malaysia.